2021
DOI: 10.1002/eqe.3578
|View full text |Cite
|
Sign up to set email alerts
|

Physical modelling of reinforced concrete at a 1:40 scale using additively manufactured reinforcement cages

Abstract: Global level assumptions of numerical models have received relatively less attention, but have been indicated to be a major source of error in numerical modeling of Reinforced Concrete (RC) structures. In parallel, it has been stated that a statistical approach involving many virgin specimens and ground motions is necessary for model validation. Such an approach would require very small‐scale testing. Then, the reinforcement fabrication becomes a major issue. This paper proposes using additive manufacturing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Following the motion‐by‐motion comparison, the numerical and experimental results of the shaking table dataset were revisited with a focus on the statistical comparison of the Cumulative Distribution Function (CDF) of key response parameters that were discussed previously. The concept of statistical validation using the CDF plots has been applied to modelling of rocking structures that showed predictable rocking responses in the statistical sense 30–32 , 35–38 . Figure 5 presents the CDF plots used for the statistical comparison in this section.…”
Section: Validation Of Numerical Modeling Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Following the motion‐by‐motion comparison, the numerical and experimental results of the shaking table dataset were revisited with a focus on the statistical comparison of the Cumulative Distribution Function (CDF) of key response parameters that were discussed previously. The concept of statistical validation using the CDF plots has been applied to modelling of rocking structures that showed predictable rocking responses in the statistical sense 30–32 , 35–38 . Figure 5 presents the CDF plots used for the statistical comparison in this section.…”
Section: Validation Of Numerical Modeling Schemementioning
confidence: 99%
“…The concept of statistical validation using the CDF plots has been applied to modelling of rocking structures that showed predictable rocking responses in the statistical sense. [30][31][32][35][36][37][38] Figure 5 presents the CDF plots used for the statistical comparison in this section. The numerical and experimental CDF plots were compared based on the Kolmogorov-Smirnov (K-S) distance 39,40 (i.e., the maximum vertical distance between the experimental and numerical CDF plots) and the relative errors (𝜀, defined as the absolute error between the experimental and numerical values divided by the experimental value) at the maximum horizontal distance, as well as at median and 90 th percentile of the experimental CDF plots, as listed in Table 1, and within each plot of Figure 5.…”
Section: Statistical Comparisonmentioning
confidence: 99%
“…In fact, this approach is consistent with the fundamental seismic design problem, which involves computing the response to a set of ground motions, rather than to an individual one. [95][96][97][98][99][100][101][102][103] For an ensemble of ground motions to be useful, in this paper all ground motions were scaled to the same PGV. PGV was used as an intensity measure, as it performs better than PGA or PGD for rocking structures.…”
Section: Rocking Spectra Resultsmentioning
confidence: 99%
“…The tests were repeatable and predictable both with FEM 81 and with DEM 82 . Notably, the concept of statistical validation could also be applied to Masonry and Reinforced Concrete structures 83,84 . Reggiani Manzo et al.…”
Section: Introductionmentioning
confidence: 89%
“…82 Notably, the concept of statistical validation could also be applied to Masonry and Reinforced Concrete structures. 83,84 Reggiani Manzo et al showed 23 that the response of a rocking structure made of precast RC elements was also predictable in the statistical sense.…”
Section: Introductionmentioning
confidence: 99%